Planning of Programmers Labor through Development of Information Systems - Tsaneva, Monika (Research Papers, 2008)
Main part of researches in the area of software project management is concentrated in direction of development time reduction, but do not refer problems of estimation of efforts, needed for task implementation and their duration. This paper suggests a methodic for estimation of planned labor-consumption and of task duration of system and application programming of business software. For this purpose, main groups of factors influencing over software development labor consumption and task performance duration have been defined as follows:Type and complexity of the software module, which is developed;Suitability of the development environment, data organization and execution framework to the software components type;Design contents and layout of the task assigned for development;Programmers qualification and motivation.An approach for estimation of the software modules complexity is proposed. The characteristics of development environment and execution framework, which are essential to efforts needed for each type of software components development, are considered.Main items of module design, which infer programming efforts, are defined.Some aspects, which determine the level of programmers’ qualification and their motivation during assigned task execution, are outlined.As a final result, a methodic for estimation of planned labor – consumption and task duration of programming of business applications software components using the defined factors, is developed.